Molecular typing and antimicrobial susceptibility testing to six antimicrobials of Clostridium difficile isolates from three Czech hospitals in Eastern Bohemia in 2011-2012 - Beran, V; Kuijper, E J; Harmanus, C; Sanders, I M; van Dorp, S M; Knetsch, C W; Janeckova, J; Seidelova, A; Barekova, L; Tvrdik, J; Chmelar, D; Ciznar, I (Folia microbiologica, 2017)
In 2011-2012, a survey was performed in three regional hospitals in the Czech Republic to determine the incidence of Clostridium difficile infections (CDIs) and to characterize bacterial isolates. C. difficile isolates were characterized by PCR ribotyping, toxin genes detection, multiple-locus variable-number tandem-repeat analysis (MLVA), and antimicrobial susceptibility testing to fidaxomicin, vancomycin, metronidazole, clindamycin, LFF571, and moxifloxacin using agar dilution method. The incidence of CDI in three studied hospitals was 145, 146, and 24 cases per 100,000 inhabitants in 2011 and 177, 258, and 67 cases per 100,000 inhabitants in 2012. A total of 64 isolates of C. difficile was available for molecular typing and antimicrobial susceptibility testing. 60.9% of the isolates were classified as ribotype 176. All 41 isolates of ribotypes 176 and 078 were positive for the presence of binary toxin genes. Ribotype 176 also carried 18-bp deletion in the regulatory gene tcdC. Tested isolates of C. difficile were fully susceptible to vancomycin and metronidazole, whereas 65.1% of the isolates were resistant to moxifloxacin. MLVA results indicated that isolates from three different hospitals were genetically related, suggesting transmission between healthcare facilities.
Keywords: Hospitals; diskové difúzní antimikrobiální testy; Molecular Typing; Česká republika; antibakteriální látky; Disk Diffusion Antimicrobial Tests; Clostridioides difficile; Clostridium Infections; incidence; klostridiové infekce; Czech Republic; lidé; Anti-Bacterial Agents; Humans; Ribotyping; Minisatellite Repeats; molekulární typizace; Bacterial Toxins; nemocnice; ribotypizace; Incidence; minisatelitní repetice; bakteriální toxiny